MOOCs: an insider’s perspective on a novel educational method with historical, organizational, participatory, and evaluative aspects (Educational Dimension, 2025)
This research investigates the role and conditions for the utilization of Massive Open Online Courses (MOOCs) in the modern educational system. The study aims to identify the evolutionary stages in the development of MOOCs, highlight the tools employed in their organization, determine the roles of the learning participants within MOOCs, and analyze the outcomes of implementing MOOCs. The research focuses on the development and proliferation of MOOCs in both global and domestic educational practices. The subject of investigation encompasses the conditions for using MOOCs in worldwide and national educational contexts. The research methodology includes analyzing regulatory acts, government programs, scientific publications, articles, monographs, and materials from scientific conferences and seminars. The findings explore the history of MOOC creation and dissemination, tracing the evolutionary transition from open content to open learning processes. The concept of a "personal learning environment" is examined, highlighting the social services involved in its formation. Practical achievements, experimental evidence, and statistical data on organizing the learning process within open distance courses are analyzed.The main conclusions and recommendations emphasize that MOOCs represent a new and underexplored method of education, incorporating novel approaches and social services that are constantly evolving. Successful implementation requires addressing key issues such as selecting and evaluating open content, assisting students in organizing activities with open content, and more. Additionally, broader questions arise, including the suitability of certain subjects for open distance courses, the integration of MOOCs into traditional teaching approaches, and the necessary pedagogical skills for conducting open distance courses.